Normal nasopharyngeal microflora as a reservoir of multiresistant strains of upper respiratory tract infections - Minukhin, V; Kovalenko, N; Tkachenko, V; Zamaziі T; Sаmusenko S; Nemchinovich, N; Shibaeva, I (Annals of Mechnikov’s Institute, 2020)
Nasopharinheal carriage of bacteria may play a central role in the development and spread of respiratory infections. In addition, so-called "healthy" carriage is often transformed under the influence of various factors into an active infection.It is necessary to take into account not only the range of possible pathogens, but also trends in the development of antibiotic resistance of leading etiologic agents while choosing tactics of antimicrobial therapy. The investigation was designed to study the role of normal microflora of the nasopharynx as a reservoir of resistant strains of respiratory infections. Materials and Methods. Fifty three healthy individuals and 168 patients with acute upper respiratory tract infections who had been treated in CEHC "Kharkiv Municipal Clinical Hospital № 30" were examined. Microbiological study included isolation and identification of pathogens in accordance with the Order of the Ministry of Health Care № 535 from 22.04.1985., determination of the sensitivity of microorganisms to antibiotics by diffusion method according to the Order of the Ministry of Health Care of Ukraine № 167 from 05.04.2007. Results and discussion. Bacteriological study of nasal swabs of healthy people showed that the composition of the microflora of the nasopharynx contained potentially pathogenic microorganisms. Among the isolated microorganisms essential place was occupied by S. epidermidis and S. aureus, both in monoculture and association. Epidermal staphylococcus was isolated in 36 % and Staphylococcus aureus in 27% of cases. Pneumococcus and hemolytic streptococcus of group A were isolated in 23 and 14% of cases, respectively. One hundred and eighty strains of opportunistic microorganisms were isolated in the study of nasopharyngeal microflora of patients with acute upper respiratory tract infection. The leading role belonged to S. pyogenes (40.5%) and S.epidermidis (33,3%). S. aureus (12,8%) and S.pneumoniae (10,6%) were next according to. The share of K. pneumoniae was within 2.8%. Research of sensitivity of selected strains to antibiotics in vitro showed correlation of indices between microorganisms isolated from the nasopharynx of healthy people and patients with acute respiratory infection. Thus, sensitivity to amoxicillin S.epidermidis, S. pneumoniae and S. pyogenes, isolated from the nasopharynx of healthy people was 81,8-84,2%, while low sensitivity to this antibiotic (66,7-83,6 % of isolated strains) was found for these microorganisms isolated from ill people. A similar trend was observed for isolated staphylococci and streptococci to clindamycin, doxycycline and ceftazidime. And on the contrary, the high activity of fluoroquinolones, chloramphenicol and ceftriaxone was observed for all microorganisms. I.e., the carriage in the nasopharynx of opportunistic pathogens with acquired antibiotic resistance is an important factor in the development of acute respiratory infections. Conclusion. 1. Facultative anaerobic microflora of nasopharynx of healthy people and patients with acute upper respiratory tract infections include opportunistic microorganisms, such as S.epidermidis, S. aureus, S. pneumoniae and S. pyogenes. 2. Bacteria, isolated from the nasopharynx of healthy people and patients with acute upper respiratory tract infections, are characterized by high levels of resistance to antibiotics of therapeutic purposes. There is a correlation between antibiotic-resistant strains circulating in a healthy population and sensitivity to antibiotics of pathogens of acute respiratory infections. 3. Levofloxacin, ciprofloxacin, ofloxacin, ceftriaxone, chloramphenicol may be used as drugs of choice for the treatment of acute upper respiratory tract infections.